PERBEDAAN KUAT TEKAN BETON MENGGUNAKAN DUA JENIS SEMEN - Rai Widiarsa, Ida Bagus (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 2 Juli 2010, 2012)
The aim of this research is to investigate the effect of using two kinds (brand) cement namely Gresik and Padang cement in one concrete mix with respect to concrete compressive strength. This research is conducted at Concrete Construction Laboratory of Engineering Faculty, Udayana University. The concrete was mixed with a ratio 1:2:3 of cement:sand:gravel, batched by volume. Five different concrete mixes were made to determine their compressive strength. The first mix used Gresik cement, the 2nd mix used Padang cement, the 3rd used a mixture of Gresik and Padang cement batched by volume 1:3, the 4th mix used a mixture of Gresik and Padang cement batched by volume 1:1, and the 5th mix used a mixture of Gresik and Padang cement batched by volume 3:1 The test results show that the concrete compressive strength, ’ bk , of the 1st, 2nd, 3rd, 4th, and the 5th mixture was 209,85 kg/cm2, 184,12 kg/cm2, 185,18 kg/cm2, 191,99 kg/cm2, and 202,10 kg/cm2 respectively.
Keywords: cement, concrete compressive strength